Evaluation of video transmission of MAC protocols in wireless sensor network - Maulidin, Maulidin; Mahmuddin, Massudi; Kamarudin, L. M. (Universiti Teknikal Malaysia Melaka, 2016)
Wireless Sensor Network (WSN) is a wireless network which consists of sensor nodes scattered in a particular area which are used to monitor physical or environment condition.Each node in WSN is also scattered in sensor field, so an appropriate scheme of MAC protocol should have to develop communication link for data transferring. Video transmission is one of the important applications for the future that can be transmitted with low aspect in side of cost and also power consumption. In this paper, comparison of five different MAC WSN protocol for video transmission namely IEEE 802.11 standard, IEEE 802.15.4 standard, CSMA/CA, Berkeley-MAC, and Lightweight-MAC protocol are studied.Simulation experiment has been conducted in OMNeT++ with INET network simulator software to evaluate the performance.Obtained results indicate that IEEE 802.11 works better than other protocol in term of packet delivery, throughput, and latency.